Sub-Nanometer Width Armchair Graphene Nanoribbon Energy Gap Atlas - Palma, Carlos-Andres; Awasthi, Manohar; Hernandez, Yenny; Feng, Xinliang; Muellen, Klaus; Niehaus, Thomas A.; Barth, Johannes V. (Journal of Physical Chemistry Letters, 2015)
Extended all-sp2-carbon macromolecules have the potential to replace silicon in integrated nanometer-scale devices. Up to now, studies on the electronic properties of such structures, for example, graphene nanoribbons, have been focused mostly on the infinitely long limit, which is inadequate when approaching future devices with sub-10 nm control. Moreover, their electronic variation has not been systematically assessed as a function of chemically diverse edge termini. Such knowledge is central when prototyping potential all-carbon circuits. Here, we present a graphene nanoribbon energy gap atlas based on density functional tight-binding spin-polarized calculations of nearly ten thousand randomly generated nanoribbons with a maximal nominal width of 1 nm and an armchair long edge. We classify ribbon families and show that their energy levels are strongly dependant on their termini edge states. We notably reveal modulation of the bulk energy gap by 0.3 eV through minimal edge modifications and put forward simple rules for inducing antiferromagnetic edge states.
CRIS-Team Scopus Importer:2023-03-20
Keywords: antiferromagnetic; density functional tight-binding theory; electronic gap; graphene nanoribbon; optical gap; polyaromatic; singlet; spin chemistry; triplet; UV Visible spectroscopy